Reanimated voices : speech reporting in a historical-pragmatic perspective - Collins, Daniel E. (Pragmatics & beyond, 2001)
Reanimated Voices addresses three activities: reporters evoking speech events; interpreters (re)constituting those speech events; and historical pragmaticians eavesdropping in time on the reporters and interpreters. Can one reconstruct aspects of pragmatic competence on the basis of written texts only? Reanimated Voices answers this in the affirmative. It offers a methodology for historical-pragmatic reconstruction to explain the synchronic patterns of variation in premodern writings. Reanimated Voices examines the distribution of reporting strategies in a corpus of medieval Russian texts. For.